2014
DOI: 10.7567/jjap.53.09pd02
|View full text |Cite
|
Sign up to set email alerts
|

Off-centering of a Bi ion in cubic phase of (Bi1/2Na1/2)TiO3

Abstract: The paraelectric cubic structure of (Bi 1/2 Na 1/2 )TiO 3 was analyzed precisely by high-energy synchrotron radiation X-ray powder diffraction measurement and the maximum entropy method (MEM)/Rietveld method. The o100p-favored rotator-like thermal behavior of the Bi ion was observed. The o100p off-centering of Bi led to the Bi-O distance of >2.5 Å that was shorter than the average Bi-O distance in the structure of the Bi on-centered model. The off-centering of Bi can be attributed to the orbital hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
(48 reference statements)
0
26
1
Order By: Relevance
“…Unlike in the pure BT and BT-based ferroelectrics, the occupancy in the partial ordering in 0.3BT-0.1BMT-0.6BF can be changed with temperature, in a particular ferroelectric phase. Recently, in solid solutions including Bi ions, such as BF-BT 46,47 and BNT 48 , offcentering of the Bi ions was observed. It was reported that the change in the Bi sites from six to ten split sites involved a phase transition from paraelectric (cubic) to ferroelectric phases (tetragonal) in K 0.5 Bi 0.5 TiO 3 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Unlike in the pure BT and BT-based ferroelectrics, the occupancy in the partial ordering in 0.3BT-0.1BMT-0.6BF can be changed with temperature, in a particular ferroelectric phase. Recently, in solid solutions including Bi ions, such as BF-BT 46,47 and BNT 48 , offcentering of the Bi ions was observed. It was reported that the change in the Bi sites from six to ten split sites involved a phase transition from paraelectric (cubic) to ferroelectric phases (tetragonal) in K 0.5 Bi 0.5 TiO 3 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Note that prior works indicate an increase in the lattice distortion upon quenching [18,23,38] and a counter effect upon annealing at 800 °C [38]. Considering that the Bi 3+ ion at the A-site exhibits off-centered displacements even for the furnace cooled specimen [41,42], it is plausible that the off-centering effects are more pronounced upon quenching. The off-centered displacements enhance further along the polar direction upon quenching [43], thus improving the lattice polarizability.…”
Section: Annealing Effects On the Conductivity Of Quenched Samplesmentioning
confidence: 90%
“…The k 33 of the q-BNLT4 ceramic is 0.47 and that of OF-BNLT4 is 0.48. Therefore, the piezoelectric activity of k 33 was not deteriorated by the quenching treatment. On the other hand, the d 33 of the q-BNLT4 ceramic is 68.8 pC=N, which is slightly lower than that of the OF-BNLT4 ceramic (80.2 pC=N).…”
Section: Introductionmentioning
confidence: 95%
“…One of the possible reasons is the "off-centering" of the Bi ion in the cubic phase at high temperature in BNT. 33) However, these are still under investigation. Figure 11 shows the piezoelectric properties (a) k 33 , (b) d 33 , and (c) " T 33 =" 0 of OF-and q-BNLBT4-100y as a function of the BT-substituted amount y.…”
Section: Introductionmentioning
confidence: 99%